2014
DOI: 10.1002/2014gl062191
|View full text |Cite
|
Sign up to set email alerts
|

Black carbon radiative forcing over the Tibetan Plateau

Abstract: We estimate the snow albedo forcing and direct radiative forcing (DRF) of black carbon (BC) in the Tibetan Plateau using a global chemical transport model in conjunction with a stochastic snow model and a radiative transfer model. The annual mean BC snow albedo forcing is 2.9 W m À2 averaged over snow-covered plateau regions, which is a factor of 3 larger than the value over global land snowpack. BC-snow internal mixing increases the albedo forcing by 40-60% compared with external mixing, and coated BC incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
0
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 112 publications
(99 citation statements)
references
References 54 publications
7
91
0
1
Order By: Relevance
“…The northern TP sites (LHG and NETP) are influenced mainly by air masses from Central Asia and partly by air masses from Eurasia, which are similar to the sources of dust reaching the TP (e.g., Zhang et al, 2016). These results are also consistent with those of He et al (2014), Kopacz et al (2011), andLu et al (2012), who modeled contributions of BC emissions in the same re- gion. In the central (TGL and NMC) and southern region (MYL and SETP) of the TP, the air masses originate mainly from Central and South Asia.…”
Section: Distributions Of Lapssupporting
confidence: 82%
See 1 more Smart Citation
“…The northern TP sites (LHG and NETP) are influenced mainly by air masses from Central Asia and partly by air masses from Eurasia, which are similar to the sources of dust reaching the TP (e.g., Zhang et al, 2016). These results are also consistent with those of He et al (2014), Kopacz et al (2011), andLu et al (2012), who modeled contributions of BC emissions in the same re- gion. In the central (TGL and NMC) and southern region (MYL and SETP) of the TP, the air masses originate mainly from Central and South Asia.…”
Section: Distributions Of Lapssupporting
confidence: 82%
“…BC in the atmosphere is mixed with OC and inorganic salts during aging enhancing its absorption (Gustafsson and Ramanathan, 2016). He et al (2014) noted that BC-snow internal mixing increases the albedo forcing by 40-60 % compared with external mixing, and coated BC increases the forcing by 30-50 % compared with uncoated BC aggregates, whereas Koch snowflakes reduce the forcing by 20-40 % relative to spherical snow grains. A lack of OC consideration due to the limitation of the SNICAR model also affected the results in this study.…”
Section: Limitations and Implications For Snow Cover And Glaciers On mentioning
confidence: 99%
“…Note that the SNICAR model we use assumes spherical snow grains and aerosolsnow external mixing for the calculation of snowpack optical properties (Flanner et al, 2007;Oleson et al, 2010). Recent studies have shown that non-spherical snow grains play a critical role in snow albedo calculations and decrease the snow albedo reductions included by LAAs compared with spherical snow grains (e.g., Liou et al, 2014;Dang et al, 2016;He et al, 2014He et al, , 2017. Nonetheless, the knowledge of snow grain shape evolution is limited and thus spherical snow grains are assumed.…”
Section: Model and Experimental Designmentioning
confidence: 99%
“…Nonetheless, the knowledge of snow grain shape evolution is limited and thus spherical snow grains are assumed. Studies have also shown the significant enhancement of solar radiation absorption with larger snow albedo reductions by aerosol-snow internal mixing compared to aerosol-snow external mixing (e.g., Flanner et al, 2012;He et al, 2014;Liou et al, 2014). However, without considering aerosol-snow internal mixing, the SNICAR model we use assumes absorption-enhancing sulfate coatings to hydrophilic BC, which can mimic BC coatings by snow and compensate for the neglect of the absorption enhancement by aerosol-snow internal mixing (Flanner et al, 2007.…”
Section: Model and Experimental Designmentioning
confidence: 99%
“…Ice crystal habit influences the spectral albedo but this effect is not fully understood yet (e.g. Libois et al, 2013;Kokhanovsky and Zege, 2004;Malinka, 2014;Liou et al, 2014;He et al, 2014).…”
Section: Introductionmentioning
confidence: 99%